If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 2) + -1(2x + -5) = 0 Reorder the terms: 4(2 + x) + -1(2x + -5) = 0 (2 * 4 + x * 4) + -1(2x + -5) = 0 (8 + 4x) + -1(2x + -5) = 0 Reorder the terms: 8 + 4x + -1(-5 + 2x) = 0 8 + 4x + (-5 * -1 + 2x * -1) = 0 8 + 4x + (5 + -2x) = 0 Reorder the terms: 8 + 5 + 4x + -2x = 0 Combine like terms: 8 + 5 = 13 13 + 4x + -2x = 0 Combine like terms: 4x + -2x = 2x 13 + 2x = 0 Solving 13 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 2x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 0 + -13 2x = 0 + -13 Combine like terms: 0 + -13 = -13 2x = -13 Divide each side by '2'. x = -6.5 Simplifying x = -6.5
| z/2=-9 | | 3m^2+8m^2-3m^2=0 | | X+2+3x-8=90 | | 4n^2+n-37=0 | | c/8=36 | | 4h-1-7h=8-15h+2 | | x^3+9x^2-10x=72 | | 7b^2-6b-4=-3 | | 5b-5-11b-9=0 | | 3(6v-8)=-132 | | 7b^2-6b-4=3 | | b/3=31 | | n-23=15 | | 5a-12=2a | | 8x^2+18x=-7 | | .680(-x)= | | -6(b+7)=-84 | | x+9-12=5-6+x-9/5 | | .500x+1x= | | 6x-7=6(x+4) | | 15c-10=-9c+2 | | 4x^2+16x=-15 | | 8(-5)=7(-5)-5 | | C^2=27 | | 5x+7=4x+18 | | 7(x-4)-6=-34 | | 4r^2+25r+32=7 | | 3(4n+6)=-114 | | -7d+5+12d=-25 | | 5c^2+19c-30=0 | | log(-m+9)=log(-2m+1) | | p=5n-7 |